2012
DOI: 10.1080/00223980.2011.637996
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parenting and Separation-Individuation in Belgian College Students: Associations with Emotional Adjustment

Abstract: The present study examined associations among perceived parenting, separation-individuation, and emotional adjustment in a convenience sample of college students in Belgium (N=350; 68% female; aged 18 to 26). In line with a conceptual model advanced in the literature, factor analysis supported the distinction between three dimensions of separation-individuation: overdependence and healthy separation (both of which had already been described in earlier research) and a new dimension, labeled excessive autonomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…This result may also reflect the Slovene culture, which allows and expects a prolonged reliance of young people on functional, emotional, and financial support of the family (Ule & Kuhar, 2003). The latter seems to have become a more general characteristic of emerging adults' life context as the finding has also been reported in other Mediterranean cultures (Mendonça & Fontaine, 2013; Saraiva & Matos, 2012; Scabini et al., 2006) and even in Western European cultures (e.g., Belgium; Delhaye, Kempenaers, Linkowski, Stroobants, & Goossens, 2012; Germany; Seiffge‐Krenke, 2006).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This result may also reflect the Slovene culture, which allows and expects a prolonged reliance of young people on functional, emotional, and financial support of the family (Ule & Kuhar, 2003). The latter seems to have become a more general characteristic of emerging adults' life context as the finding has also been reported in other Mediterranean cultures (Mendonça & Fontaine, 2013; Saraiva & Matos, 2012; Scabini et al., 2006) and even in Western European cultures (e.g., Belgium; Delhaye, Kempenaers, Linkowski, Stroobants, & Goossens, 2012; Germany; Seiffge‐Krenke, 2006).…”
Section: Discussionsupporting
confidence: 72%
“…It thus seems that maintenance of connected parent–child relationships and emerging adults' opportunities to express autonomy within the family context are different aspects of the same developmental course leading to psychosocial maturity and personal satisfaction. Coherent with theory (for an overview, see Koepke & Denissen, 2012) and with existing research linking individuation with college adjustment (Beyers & Goossens, 2003; Lamborn & Groh, 2009), general adjustment (as indicated by lower psychological and somatic symptoms, and stronger self‐esteem; Lamborn & Groh, 2009), and emotional adjustment (Delhaye, Kempenaers, Linkowski, et al., 2012), our study gives further support that a balance between two opposing tendencies, i.e., striving for independence from parents and yet trying to remain connected to them, plays an important role in successful transition to adulthood. Our findings also imply that the three individuation measures provide more predictive information in explaining emerging adults' life satisfaction than the ACA.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These studies have also shown that high levels of emotional autonomy are associated with challenges in family relationships during adolescence and emerging adulthood, less cohesive family structures marked by a lack of emotional intimacy and communication, and more difficult parent‐child relationships (Neff & Harter, ; Yu, ). Thus, according to this latter perspective, high emotional autonomy is associated, at least during these years, with feelings of insecurity, negative self‐concept, depression and other behaviors linked to internalizing problems (Delhaye, Kempenaers, Linkowski, Stroobants & Goossens, ; Ryan & Lynch, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bu bulgu alanyazında yer alan çalışmalarla tutarlı olarak ebeveynlik yaklaşımlarının özerklik ile yakından ilişkili olduğunu göstermektedir (Steinberg, 1987;Frank, Pirsch ve Wright, 1990;Hines, 1997;Beyers ve Gossens, 1999;Deslandes ve Potvin, 1999;Musaağaoğlu ve Güre, 2005). Çalışmanın bulgusuyla tutarlı olmayan bir çalışma üniversite öğrencileriyle yapılmış, özerklikle bağlantılı olan ayrışma-bireyleşme ile ebeveynlik biçimleri ilişkili bulunmamıştır (Delhaye, Kempenaers, Linkowski, Stroobants and Goossens, 2012).…”
Section: Discussionunclassified